1980
DOI: 10.1530/jrf.0.0600193
|View full text |Cite
|
Sign up to set email alerts
|

Development of the gonad in normal and anencephalic human fetuses

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…In hypophysectomized fetal sheep, the resulting reduction in testis size and tubule diameter (Liggins & Kennedy 1968) would also be consistent with reduced gonocyte numbers. Similarly, in anencephalic humans, it is reported that gonocyte/prespermatogonial numbers appear reduced (Baker & Scrimgeour 1980). Therefore, it is likely that gonocyte proliferation and survival during fetal development in most species are pituitary-dependent in the latter parts of gestation, although this effect is likely to be mediated through Sertoli cell number and activity.…”
Section: Germ Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In hypophysectomized fetal sheep, the resulting reduction in testis size and tubule diameter (Liggins & Kennedy 1968) would also be consistent with reduced gonocyte numbers. Similarly, in anencephalic humans, it is reported that gonocyte/prespermatogonial numbers appear reduced (Baker & Scrimgeour 1980). Therefore, it is likely that gonocyte proliferation and survival during fetal development in most species are pituitary-dependent in the latter parts of gestation, although this effect is likely to be mediated through Sertoli cell number and activity.…”
Section: Germ Cellsmentioning
confidence: 99%
“…As hCG levels decline, however, towards the end of the second trimester, fetal LH may become more important in maintaining Leydig cell function (Fowler et al , 2009). Interestingly, in anencephalic human fetuses, studied in the late second and third trimesters, there is an apparent loss of fetal Leydig cells (Baker & Scrimgeour 1980), and the external genitalia are often small in newborns (Scott et al 2009). Similarly, hypophysectomy in the last third of gestation reduces the overall percentage of Leydig cells at term in the rhesus monkey (Gulyas et al 1977).…”
Section: Endocrinology Of the Fetal Testismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of pituitary gonadotrophins in ovarian development and function during foetal life is not well understood. In anencephalic female foetuses, normal follicular development up to 34 weeks of gestation is observed but, thereafter, large growing follicles that are common in healthy foetuses are not seen in anencephalic female foetuses [16]. This finding suggests that ovarian development up to the 7th month of pregnancy occurs independently of stimulation by the foetal hypothalamus, but pituitary gonadotrophins later have a role in follicular growth.…”
Section: Introductionmentioning
confidence: 99%
“…In the human [57] and rhesus monkey [58,59], fetal anencephaly, which results in a loss of pituitary gonadotropin secretion, is associated with a reduction in testes weight, germ cell numbers, and testosterone production. These findings, plus the observation that the human fetal testis expresses the receptors for FSH [60] and LH [61], support the suggestion that FSH and LH regulate fetal testis development [62].…”
Section: Discussionmentioning
confidence: 99%